The Impact of Surgical Margin Distance on Local Recurrence and Survival in Patients with Soft Tissue Sarcoma - Alparslan Yurtbay; Şafak Aydın Şimşek; Tolgahan Cengiz; Yakup Sancar Bariş; Ferhat Say; Nevzat Dabak (Medicina)
Background and Objectives: The primary objective of surgeons treating bone and soft tissue sarcomas (STS) is to achieve optimal local tumor control, ensuring a tumor-free margin and preventing local recurrence. However, the impact of surgical resection margin status on extremity STSs remains an area that requires further exploration. Therefore, this study aims to investigate the effects of surgical resection margin status on both local recurrence and overall survival rates. Materials and Methods: One hundred and eighty-five patients who underwent surgical resection with a diagnosis of soft tissue sarcoma were studied. The study recorded patient demographics, tumor characteristics, surgical margin distance (in millimeters), and disease-related outcomes. Results: The minimum follow-up period was 24 months (24–168). The mean time to local recurrence after resection was 103.2 months (95% CI 91.73 to 114.64). The mean local recurrence-free survival was found to be 7.23 months in patients with positive surgical margins, 87.42 months in patients with ≤1 mm, and 139.80 months in patients with >1 mm (p < 0.001). Patients with surgical margins ≤1 mm were more likely to have local recurrence than patients with >1 mm (0.41 [0.21–0.81], p = 0.010). The mean overall survival was 106.72 months (95% CI 95.98 to 117.46). Positive surgical margins were associated with decreased overall survival (3.58 [1.46–8.80], p = 0.005). There was a statistically significant difference between the histologic grade in terms of local recurrence (4.50 [95% CI 2.57 to 7.88]; p < 0.001) and overall survival (3.12 [95% CI 1.52 to 6.41]; p = 0.002). Conclusions: Achieving a negative surgical margin distance of more than 1 mm appears to be correlated with a reduced risk of local recurrence. Positive surgical margins are a risk factor that detrimentally impacts overall patient survival. However, determining the appropriate margin distance for all patients poses a significant challenge.